Therapeutic Outcomes Following Uterine Lavage, Levamisole, PGF2α and their Combinations in Subclinical Endometritic Buffaloes - Singh, N.; Singh, B.; Kumar, R. (The Indian Journal of Animal Reproduction, 2021)
This study examined the effect of different therapeutic protocols on macro-mineral profile and reproductive performance of endometritic buffaloes. Endometritic buffaloes were assigned in five treatment and one control groups viz. uterine lavage (UL), Levamisole (LEV), PGF2α (PG), Uterine lavage+Levamisole (UL+LEV), Uterine lavage+PGF2α (UL+PG) and control (no therapy) consisting of six buffaloes in each group. The Subclinical endometritic buffaloes were diagnosed using White side test. The screened buffaloes were subjected to different treatment regimen as mentioned earlier. It was observed that the post-treatment calcium and phosphorus level was significantly (P<0.05) higher in all treatment groups as compared to their corresponding pre-treatment values, whereas no significant (P>0.05) change was recorded in control group. The clinical cure rate of endometritis was 33.33, 50.00, 66.67, 66.67, 83.33 and 83.33% in untreated control, UL, LEV, PG, UL+LEV and UL+PG, respectively. The corresponding conception rates were 16.67, 33.33, 50.00, 50.00, 66.67 and 66.67% in in untreated control, UL, LEV, PG, UL+LEV and UL+PG, respectively. The results inferred that, uterine lavage along with levamisole or PGF2α can be used effectively to manage endometritic buffaloes.